Implementasi Kurikulum Merdeka Di SMP Negeri 2 Malang - Alfarizi, Mochamad Naufal; Wiguna, Artha Hadi; Zahraafi (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
This study focuses on the implementation of the Independent Curriculum (Kurikulum Merdeka) at SMP Negeri 2 Malang, particularly in the Science subject. The primary objective is to explore the extent to which the principles of the Independent Curriculum are applied in the school. Employing a qualitative approach, the research collected data through observations and interviews with teachers and students. The findings reveal that the learning approaches used in the school are student-centered, contextual, and project-based. Teachers act as facilitators, employing diverse methods such as discussions, experiments, and educational technology. Evaluation is conducted continuously by both teachers and students through reflective practices. Furthermore, the study shows that the Independent Curriculum enhances student engagement, character development, and personalized learning based on individual interests and needs. Overall, the findings suggest that the implementation of the Independent Curriculum at SMP Negeri 2 Malang is effective and aligns with the fundamental principles established by the Ministry of Education, Culture, Research, and Technology.